TEACHING EXPERIENCE AND ITS ROLE IN FOREIGN LANGUAGE TEACHERS’ ANXIETY - Jedynak, Małgorzata (Acta Neophilologica, 2011)
Twelve teachers of English representing three groups of different seniority: pre-service, freshmen and senior responded to the anxiety questionnaire to establish the relationship between the anxiety level and their teaching experience. The senior group is reported to have experienced less anxiety than other teachers. Some influential factors which determine a level of this specific anxiety were identified, for example expectations towards their work, autonomy in taking deci- sions, interactions with authorities, superiors and students. Finally, the article discusses practical ways of coping with teacher anxiety in a classroom.